Preparation method and application of novel imprinting detection test paper capable of adsorbing cobalt ions layer by layer
By using layer-by-layer adsorption method to construct a multi-layer film on the modified polyacrylonitrile film, the problems of low sensitivity and high cost of cobalt ion detection in the prior art are solved, and high sensitivity, fast and low-cost cobalt ion detection are achieved.
Patent Information
- Application Number
- CN202411653539.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-03-18
AI Technical Summary
The prior art has lower sensitivity when detecting trace amounts or even lower concentrations of cobalt ions in water, and is inconvenient on-site analysis and is costly.
The ion-blotting adsorption layer was constructed by layer-by-layer adsorption method, and the multi-layer film was prepared by alternating deposition on the modified polyacrylonitrile film through electrostatic force interaction, shortening the time required for cobalt ion adsorption saturation.
It significantly improves the detection sensitivity of cobalt ions, shortens detection time, reduces cost, and improves the accuracy and reliability of detection.
Smart Images

Figure CN119643536A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of ion detection, and in particular relates to a preparation method and application of a novel layer-by-layer adsorption cobalt ion imprinting detection test paper. Background Art
[0002] Cobalt has the advantages of ferromagnetism, oxidation resistance and high hardness, and has been widely used in industrial production such as cemented carbide, magnetic materials, electronics, chemicals, and ceramics. In the production and use of cobalt and its isotopes, a large amount of cobalt-containing wastewater will be generated. These wastewaters not only harm the environment, but also have irreversible effects on the health of humans and animals, such as goiter, paralysis, and bone defects. Therefore, the establishment of cobalt ion (Co 2+ ) detection is particularly important.
[0003] The detection of cobalt ion content is of great significance in the fields of environmental testing, industrial production, medicine, food safety, etc. Common detection methods for cobalt elements mainly include electrochemical method, spectrophotometry, chemiluminescence method, etc. This type of detection method has low sensitivity and is not suitable for the detection of trace or even lower concentrations of cobalt ions in water. X-ray fluorescence spectroscopy, atomic absorption spectroscopy, inductively coupled plasma spectroscopy, etc., this type of detection instrumentation is relatively expensive, the measurement cost is high, and it is not suitable for on-site online analysis. Therefore, it is particularly important to develop a highly sensitive and low-cost on-site method for detecting cobalt ions.
[0004] Ion imprinting is an efficient adsorption and separation technology that can selectively adsorb and recover specific ions in complex environmental systems. The steps are as follows: first, a monomer-imprinted ion complex is formed between the functional monomer and the imprinted ion; then, under the action of a cross-linking agent, the functional groups on the monomer are arranged and fixed in a directional manner to form a stable ion-imprinted polymer. Finally, an eluent is added to elute the imprinted ions. In this way, a three-dimensional cavity with the same size and structure as the imprinted ion is formed in the imprinted polymer. This cavity can effectively reselect and identify the target ion. The ion imprinted test paper made by ion imprinting has a higher sensitivity, but the time to reach adsorption saturation is often longer. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a preparation method and application of a novel layer-by-layer adsorption cobalt ion imprinting detection test paper.
[0006] The present invention constructs an ion imprinting adsorption layer by a layer-by-layer adsorption method based on the ion imprinting technology to achieve multi-layer adsorption, further shortening the time required for adsorption saturation. The cobalt ion detection test paper prepared by the present invention is suitable for mass production and helps to promote the industrialization of the cobalt ion detection test paper.
[0007] A novel method for preparing a layer-by-layer adsorption cobalt ion imprinting test paper is specifically completed in the following steps:
[0008] 1. Pretreatment of support membrane:
[0009] First, immerse the basement membrane in a NaOH solution, then heat and hydrolyze for a period of time, then take out the basement membrane, and use deionized water to rinse the basement membrane until it is neutral to obtain a hydrolyzed basement membrane; store the hydrolyzed basement membrane in deionized water for later use;
[0010] 2. Preparation of polyelectrolyte solution:
[0011] ①, CoCl2·6H2O, acrylamide and polyethyleneimine aqueous solution were mixed evenly, reacted at 60℃~65℃ for a period of time, then a crosslinking agent and an initiator were added, and ultrasonic degassing was performed at room temperature for a period of time to obtain a polycationic polymerization aqueous solution;
[0012] ②, dissolving polyacrylic acid in deionized water to obtain a polyanion aqueous solution;
[0013] 3. Preparation of cobalt ion imprinted test paper:
[0014] The hydrolyzed base film is dried, and then the dried base film is first immersed in a polycation polymerization aqueous solution for adsorption for a period of time, and then rinsed with deionized water, and then immersed in a polyanion aqueous solution for adsorption for a period of time; after being taken out, it is rinsed with HCl aqueous solution for multiple times until Co is not detected in the washing liquid. 2+ The mixture is dried and cut to obtain a novel layer-by-layer adsorption cobalt ion imprinting test paper.
[0015] The novel layer-by-layer adsorption cobalt ion imprinting test paper is used for qualitative or quantitative detection of cobalt ions.
[0016] Principle of the present invention:
[0017] The present invention combines ion imprinting technology with membrane separation technology to prepare a new type of layer-by-layer adsorption cobalt ion imprinting detection test paper. As a new type of functional material preparation method, ion imprinting technology has the advantages of strong selectivity, high sensitivity, strong chemical stability, good anti-interference ability, etc., and has become an important means in the field of heavy metal detection. The test paper prepared by ion imprinting technology can specifically identify and selectively adsorb target ions, and complete qualitative and quantitative analysis of target ions.
[0018] Advantages of the present invention:
[0019] 1. The present invention adopts layer-by-layer adsorption technology to prepare a new type of layer-by-layer adsorption cobalt ion imprinting detection test paper for cobalt ion concentration detection, and prepares an ion imprinting multilayer membrane by alternate deposition on a modified polyacrylonitrile (PAN) membrane through electrostatic force interaction; compared with the traditional ion imprinting adsorption membrane, the cobalt ion imprinting membrane (Co-IIM) prepared by the present invention belongs to multilayer adsorption, which greatly shortens the time required to reach adsorption saturation and is convenient for rapid detection; by observing the change of surface color of Co-IIM during the adsorption process, the membrane can be used for qualitative concentration detection of cobalt ions in aqueous solution, and the prepared Co-IIM can quantitatively detect cobalt ions in the range of 0.01mgL-2mgL, and wastewater beyond this detection range can be simply diluted before measurement;
[0020] 2. A novel layer-by-layer adsorption cobalt ion imprinting test paper prepared by the present invention greatly shortens the detection time. The test paper is easy to carry, has high sensitivity, low cost, simple preparation and easy storage;
[0021] 3. Ion imprinting technology has strong anti-interference performance and can achieve specific recognition and selective adsorption of cobalt ions, completing qualitative and quantitative detection of cobalt ions;
[0022] 4. After immersing the color test paper in the test solution and comparing it with the standard sample, the concentration range of cobalt ions can be determined; according to the color development of the test paper, the cobalt ion concentration can be quantitatively analyzed. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The following are photos of the test paper standard samples of cobalt ions of different concentrations obtained in step 1 of Example 1;
[0024] Figure 2 This is the detection situation of different ions in 0.5 mg / L cobalt ion standard solution. DETAILED DESCRIPTION
[0025] Specific implementation method 1: This implementation method is a novel method for preparing a layer-by-layer adsorption cobalt ion imprinting test paper, which is specifically completed according to the following steps:
[0026] 1. Pretreatment of support membrane:
[0027] First, immerse the basement membrane in a NaOH solution, then heat and hydrolyze for a period of time, then take out the basement membrane, and use deionized water to rinse the basement membrane until it is neutral to obtain a hydrolyzed basement membrane; store the hydrolyzed basement membrane in deionized water for later use;
[0028] 2. Preparation of polyelectrolyte solution:
[0029] ①, CoCl2·6H2O, acrylamide and polyethyleneimine aqueous solution were mixed evenly, reacted at 60℃~65℃ for a period of time, then a crosslinking agent and an initiator were added, and ultrasonic degassing was performed at room temperature for a period of time to obtain a polycationic polymerization aqueous solution;
[0030] ②, dissolving polyacrylic acid in deionized water to obtain a polyanion aqueous solution;
[0031] 3. Preparation of cobalt ion imprinted test paper:
[0032] The hydrolyzed base film is dried, and then the dried base film is first immersed in a polycation polymerization aqueous solution for adsorption for a period of time, and then rinsed with deionized water, and then immersed in a polyanion aqueous solution for adsorption for a period of time; after being taken out, it is rinsed with HCl aqueous solution for multiple times until Co is not detected in the washing liquid. 2+ The mixture is dried and cut to obtain a novel layer-by-layer adsorption cobalt ion imprinting test paper.
[0033] Specific embodiment 2: This embodiment differs from specific embodiment 1 in that: the base membrane in step 1 is a polyacrylonitrile ultrafiltration membrane; the concentration of the NaOH solution in step 1 is 1.5 mol / L to 2.5 mol / L; the temperature of the hydrolysis in step 1 is 60°C to 65°C, and the time of the hydrolysis is 20min to 40min. The other steps are the same as those in specific embodiment 1.
[0034] Specific implementation method 3: This implementation method is different from specific implementation method 1 or 2 in that: the crosslinking agent in step 2① is ethylene glycol dimethacrylate; the initiator in step 2① is azobisisobutyronitrile. The other steps are the same as those in specific implementation method 1 or 2.
[0035] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that: the concentration of the polyethyleneimine aqueous solution in step 2① is 3g / L; the solid content of the polyethyleneimine in step 2① is 50%, Mw=70000g / mol; the reaction time at 60℃~65℃ in step 2① is 1h~3h. The other steps are the same as those in specific embodiments 1 to 3.
[0036] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that: the mass volume ratio of CoCl2·6H2O, acrylamide and polyethyleneimine aqueous solution described in step 2① is 0.024g:(0.014g~0.056g):100mL; the mass ratio of CoCl2·6H2O, crosslinking agent and initiator described in step 2① is 0.024g:(0.164mg~0.656mg):10mg; the time of ultrasonic degassing described in step 2① is 5min~10min. The other steps are the same as those of specific embodiments 1 to 4.
[0037] Specific embodiment 6: This embodiment differs from specific embodiments 1 to 5 in that: the concentration of the polyanion aqueous solution in step 2 ② is 3 g / L; the polyacrylic acid in step 2 ② is a viscous liquid with a solid content of 40% and Mw = 5000 g / mol. The other steps are the same as those in specific embodiments 1 to 5.
[0038] Specific embodiment 7: This embodiment differs from specific embodiments 1 to 6 in that: in step 3, the dried base film is first immersed in the polycation polymerization aqueous solution for adsorption for 40min to 50min; the number of times of rinsing with deionized water after taking out in step 3 is 2 to 3 times; the time of immersion in the polyanion aqueous solution for adsorption in step 3 is 40min to 50min; the mass fraction of the HCl aqueous solution in step 3 is 5%; the drying temperature in step 3 is 60℃ to 65℃. The other steps are the same as those in specific embodiments 1 to 6.
[0039] Specific implementation method eight: This implementation method is a novel layer-by-layer adsorption of cobalt ions imprinting test paper for qualitative or quantitative detection of cobalt ions.
[0040] Specific embodiment 9: The difference between this embodiment and specific embodiments 1 to 8 is that the method for qualitatively detecting cobalt ions by using the new layer-by-layer adsorption cobalt ion imprinting test paper is:
[0041] The novel layer-by-layer adsorption cobalt ion imprinting test paper is immersed in the solution to be tested for 2-3 minutes, and its color change is observed. If the color changes from white to purple-red, the solution to be tested contains cobalt ions. The other steps are the same as those in the first to eighth embodiments.
[0042] Specific embodiment 10: The difference between this embodiment and specific embodiments 1 to 9 is that the method for quantitatively detecting cobalt ions by the new layer-by-layer adsorption cobalt ion imprinting test paper is:
[0043] 1. Preparation of cobalt ion test paper standard:
[0044] Using cobalt chloride as a cobalt ion source, cobalt ion standard solutions with concentrations of 0.01 mg / L, 0.5 mg / L, 1 mg / L, and 2 mg / L were prepared; 4 new layer-by-layer adsorption cobalt ion imprinting test papers were immersed in the cobalt ion standard solutions with concentrations of 0.01 mg / L, 0.5 mg / L, 1 mg / L, and 2 mg / L for 2 min to 5 min, taken out and dried to obtain test paper standard samples of cobalt ions with different concentrations;
[0045] 2. Quantitative detection:
[0046] The new layer-by-layer adsorption cobalt ion imprinting test paper is immersed in the solution to be tested for 2-5 minutes, taken out and dried, and then the color-developed test paper is compared with the test paper standard samples of cobalt ions of different concentrations to determine the content of cobalt ions. The other steps are the same as those of the first to ninth embodiments.
[0047] The following examples are used to verify the beneficial effects of the present invention:
[0048] Example 1: A method for preparing a novel layer-by-layer adsorption cobalt ion imprinting test paper is specifically completed according to the following steps:
[0049] 1. Pretreatment of support membrane:
[0050] First, immerse the basement membrane in a NaOH solution, then heat and hydrolyze for a period of time, then take out the basement membrane, and use deionized water to rinse the basement membrane until it is neutral to obtain a hydrolyzed basement membrane; store the hydrolyzed basement membrane in deionized water for later use;
[0051] The base membrane described in step 1 is a polyacrylonitrile ultrafiltration membrane (PAN);
[0052] The concentration of the NaOH solution described in step 1 is 2 mol / L;
[0053] The temperature of the hydrolysis in step 1 is 75°C, and the time of the hydrolysis is 30 minutes;
[0054] 2. Preparation of polyelectrolyte solution:
[0055] ① CoCl2·6H2O, acrylamide (AM) and polyethyleneimine aqueous solution were mixed evenly, reacted at 65°C for 2h, and then a crosslinking agent and an initiator were added, and ultrasonic degassing was performed at room temperature for 10min to obtain a polycationic polymerization aqueous solution;
[0056] The concentration of the polyethyleneimine aqueous solution described in step 2① is 3g / L; the solid content of the polyethyleneimine described in step 2① is 50%, Mw=70000g / mol;
[0057] The cross-linking agent described in step 2① is ethylene glycol dimethacrylate (EDGMA);
[0058] The initiator described in step 2① is azobisisobutyronitrile (AIBN);
[0059] The mass volume ratio of the CoCl2·6H2O, acrylamide and polyethyleneimine aqueous solution described in step 2① is 0.024g:0.014g:100mL;
[0060] The mass ratio of CoCl2·6H2O, crosslinking agent and initiator described in step 2① is 0.024g:0.328g:10mg;
[0061] ②, dissolving polyacrylic acid in deionized water to obtain a polyanion aqueous solution;
[0062] The concentration of the polyanion aqueous solution described in step 2② is 3g / L;
[0063] The polyacrylic acid described in step 2② is a viscous liquid with a solid content of 40% and Mw=5000 g / mol;
[0064] 3. Preparation of cobalt ion imprinted test paper:
[0065] The hydrolyzed base film was dried, and then the dried base film was first immersed in a polycation polymerization aqueous solution for adsorption for a period of time, and then rinsed with deionized water for 3 times, and then immersed in a polyanion aqueous solution for adsorption for a period of time; after being taken out, it was rinsed with a 5% HCl aqueous solution for multiple times until no Co was detected in the washing liquid. 2+ The mixture was dried at 65°C and cut to obtain a novel layer-by-layer adsorption cobalt ion imprinting test paper.
[0066] In step 3, the dried basement membrane is first immersed in the polycationic polymerization solution for an adsorption time of 45 minutes;
[0067] In step 3, the adsorption time in the polyanion solution is 45 minutes.
[0068] Example 2: The difference between this example and Example 1 is that the mass volume ratio of CoCl2·6H2O, acrylamide and polyethyleneimine aqueous solution described in step 2① is 0.024g:0.028g:100mL. The other steps and parameters are the same as those in Example 1.
[0069] Example 3: The difference between this example and Example 1 is that the mass volume ratio of CoCl2·6H2O, acrylamide and polyethyleneimine aqueous solution described in step 2① is 0.024g:0.042g:100mL. The other steps and parameters are the same as those in Example 1.
[0070] Example 4: The difference between this example and Example 1 is that the mass volume ratio of CoCl2·6H2O, acrylamide and polyethyleneimine aqueous solution described in step 2① is 0.024g:0.056g:100mL. The other steps and parameters are the same as those in Example 1.
[0071] Example 5: The difference between this example and Example 1 is that the mass volume ratio of CoCl2·6H2O, acrylamide and polyethyleneimine aqueous solution described in step 2① is 0.024g:0.042g:100mL; the mass ratio of CoCl2·6H2O, crosslinking agent and initiator described in step 2① is 0.024g:0.164g:10mg. Other steps and parameters are the same as those in Example 1.
[0072] Example 6: The difference between this example and Example 1 is that the mass volume ratio of CoCl2·6H2O, acrylamide and polyethyleneimine aqueous solution described in step 2① is 0.024g:0.048g:100mL; the mass ratio of CoCl2·6H2O, crosslinking agent and initiator described in step 2① is 0.024g:0.492g:10mg. Other steps and parameters are the same as those in Example 1.
[0073] Example 7: The difference between this example and Example 1 is that the mass volume ratio of CoCl2·6H2O, acrylamide and polyethyleneimine aqueous solution described in step 2① is 0.024g:0.048g:100mL; the mass ratio of CoCl2·6H2O, crosslinking agent and initiator described in step 2① is 0.024g:0.656g:10mg. Other steps and parameters are the same as those in Example 1.
[0074] Application Example 1: A novel layer-by-layer adsorption of cobalt ions imprinting test paper prepared in Example 1 is used to quantitatively detect cobalt ions, specifically:
[0075] 1. Preparation of cobalt ion test paper standard:
[0076] Using cobalt chloride as the cobalt ion source, prepare cobalt ion standard solutions with concentrations of 0.01 mg / L, 0.5 mg / L, 1 mg / L, and 2 mg / L; immerse 4 new layer-by-layer adsorption cobalt ion imprinting test papers in the cobalt ion standard solutions with concentrations of 0.01 mg / L, 0.5 mg / L, 1 mg / L, and 2 mg / L for 2-5 minutes, take out and dry, and obtain test paper standard samples of cobalt ions with different concentrations (see Figure 1 shown);
[0077] 2. Quantitative detection:
[0078] The new layer-by-layer adsorption cobalt ion imprinting test paper is immersed in the solution to be tested for 5 minutes, and the test paper changes from white to purple-red. The colored test paper is then compared with the test paper standards of different cobalt ion concentrations to determine the cobalt ion content.
[0079] Application Example 2: Sodium chloride, potassium hydroxide, anhydrous calcium chloride, magnesium chloride, anhydrous ferric sulfate, copper sulfate, and manganese chloride are used to prepare a 0.5 mg / L Na + , K + , Ca 2+ Mg 2+ , Fe 2+ , Cu 2+ , Mn 2+ The obtained solutions were added dropwise onto the prepared test paper. Figure 2 As shown;
[0080] from Figure 2 It can be observed that the test paper only has a color reaction to cobalt ions.
Claims
1. A novel method for preparing a layer-by-layer adsorption cobalt ion imprinting test paper, characterized in that The preparation method is specifically completed according to the following steps:
1. Pretreatment of support membrane: First, immerse the basement membrane in a NaOH solution, then heat and hydrolyze for a period of time, then take out the basement membrane, and use deionized water to rinse the basement membrane until it is neutral to obtain a hydrolyzed basement membrane; store the hydrolyzed basement membrane in deionized water for later use; 2. Preparation of polyelectrolyte solution: ①, CoCl2·6H2O, acrylamide and polyethyleneimine aqueous solution were mixed evenly, reacted at 60℃~65℃ for a period of time, then a crosslinking agent and an initiator were added, and ultrasonic degassing was performed at room temperature for a period of time to obtain a polycationic polymerization aqueous solution; ②, dissolving polyacrylic acid in deionized water to obtain a polyanion aqueous solution; 3. Preparation of cobalt ion imprinted test paper: The hydrolyzed base film is dried, and then the dried base film is first immersed in a polycation polymerization aqueous solution for adsorption for a period of time, and then rinsed with deionized water, and then immersed in a polyanion aqueous solution for adsorption for a period of time; after being taken out, it is rinsed with HCl aqueous solution for multiple times until Co is not detected in the washing liquid. 2+ The mixture is dried and cut to obtain a novel layer-by-layer adsorption cobalt ion imprinting test paper.
2. The method for preparing a novel layer-by-layer adsorption cobalt ion imprinting test paper according to claim 1, characterized in that The base membrane described in step one is a polyacrylonitrile ultrafiltration membrane; the concentration of the NaOH solution described in step one is 1.5 mol / L to 2.5 mol / L; the temperature of the heating hydrolysis described in step one is 60° C. to 65° C., and the time of the heating hydrolysis is 20 min to 40 min.
3. The method for preparing a novel layer-by-layer adsorption cobalt ion imprinting test paper according to claim 1, characterized in that The crosslinking agent described in step 2① is ethylene glycol dimethacrylate; the initiator described in step 2① is azobisisobutyronitrile.
4. The method for preparing a novel layer-by-layer adsorption cobalt ion imprinting test paper according to claim 1, characterized in that The concentration of the polyethyleneimine aqueous solution described in step 2① is 3g / L; the solid content of the polyethyleneimine described in step 2① is 50%, Mw=70000g / mol; the reaction time at 60℃~65℃ in step 2① is 1h~3h.
5. The method for preparing a novel layer-by-layer adsorption cobalt ion imprinting test paper according to claim 1, characterized in that The mass volume ratio of CoCl2·6H2O, acrylamide and polyethyleneimine aqueous solution described in step 2① is 0.024g:(0.014g~0.056g):100mL; the mass ratio of CoCl2·6H2O, crosslinker and initiator described in step 2① is 0.024g:(0.164mg~0.656mg):10mg; the time of ultrasonic degassing described in step 2① is 5min~10min.
6. The method for preparing a novel layer-by-layer adsorption cobalt ion imprinting test paper according to claim 1, characterized in that The concentration of the polyanion aqueous solution described in step 2② is 3 g / L; the polyacrylic acid described in step 2② is a viscous liquid with a solid content of 40% and Mw=5000 g / mol.
7. The method for preparing a novel layer-by-layer adsorption cobalt ion imprinting test paper according to claim 1, characterized in that In step three, the dried base membrane is first immersed in a polycationic polymerization aqueous solution for an adsorption time of 40 to 50 minutes; after being taken out in step three, it is rinsed with deionized water 2 to 3 times; in step three, it is immersed in a polyanion aqueous solution for an adsorption time of 40 to 50 minutes; the mass fraction of the HCl aqueous solution described in step three is 5%; the drying temperature described in step three is 60°C to 65°C.
8. Application of a novel layer-by-layer adsorption cobalt ion imprinting test paper prepared by the preparation method according to claim 1, characterized in that The novel layer-by-layer adsorption cobalt ion imprinting test paper is used for qualitative or quantitative detection of cobalt ions.
9. The use of a novel layer-by-layer adsorption cobalt ion imprinting test paper according to claim 8, characterized in that The method for qualitative detection of cobalt ions by the new layer-by-layer adsorption cobalt ion imprinting test paper is as follows: The novel layer-by-layer adsorption cobalt ion imprinting test paper is immersed in the solution to be tested for 2 to 3 minutes, and its color change is observed. If its color changes from white to purple-red, it means that the solution to be tested contains cobalt ions.
10. The use of a novel layer-by-layer adsorption cobalt ion imprinting test paper according to claim 8, characterized in that The method for quantitative detection of cobalt ions by the new layer-by-layer adsorption cobalt ion imprinting test paper is as follows:
1. Preparation of cobalt ion test paper standard: Using cobalt chloride as a cobalt ion source, cobalt ion standard solutions with concentrations of 0.01 mg / L, 0.5 mg / L, 1 mg / L, and 2 mg / L were prepared; 4 new layer-by-layer adsorption cobalt ion imprinting test papers were immersed in the cobalt ion standard solutions with concentrations of 0.01 mg / L, 0.5 mg / L, 1 mg / L, and 2 mg / L for 2 min to 5 min, taken out and dried to obtain test paper standard samples of cobalt ions with different concentrations; 2. Quantitative detection: The novel layer-by-layer adsorption cobalt ion imprinting test paper is immersed in the solution to be tested for 2 to 5 minutes, taken out and dried, and then the colored test paper is compared with the test paper standard samples of cobalt ions of different concentrations to determine the content of cobalt ions.